Intra-Party Conflicts and Party Stability in Nigeria: A Study of the Alliance for Democracy (AD) - Adenuga, Gbeke; Adenuga, Adetoun; Oderinde, Oluwadamilola (goodwood publishing, 2021)
Purpose: The study examined the effects of the strategies employed by the Alliance for Democracy (AD), the main opposition party in the 1999 general elections in Nigeria, to manage its internal conflicts. Research methodology: This study is qualitative. It analyzed secondary data on Nigeria’s Fourth Republic to explain the management of intra-party conflicts in the Alliance for Democracy (AD). Results: It found that the AD was able to record remarkable successes in the 1998/1999 general elections as a result of its internal mechanism for mediation, bargaining, consultations, and negotiations among the party members. However, its inability to employ effective management strategies to settle internal crises before and after the 2003 general elections signaled the loss of its status as one of the leading parties in the country. Limitations: Despite being the main opposition party in the 1999 general elections, literature on the AD is scanty. This limited insights into events that culminated in the AD’s loss of status as a frontline political party in Nigeria. Contribution: It enriches the literature on the causes of intra-party conflicts and the effects of mismanaging such conflicts on party stability. It also provides deep insights into the reasons for AD’s loss of status from being the main opposition party in Nigeria between 1999 and 2003 to being deregistered in 2020.